1981
DOI: 10.1016/0378-5955(81)90033-2
|View full text |Cite
|
Sign up to set email alerts
|

Adenylate cyclase activity in the fetal and the early postnatal inner ear of the mouse

Abstract: The adenylate cyclase activity was analyzed in fetal, early postnatal and adult inner ears of the CBA/CBA mouse and also in approximately one month old inner ears from Shaker -1 and Shaker -2 mice. A comparison was made with the maturation of potassium levels in endolymph as investigated with the X-ray energy dispersive technique. Adenylate cyclase activity in the developing normal inner ear shows two significant periods of increases: from the 16th to the 19th gestational day in both the cochlear and vestibula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

1983
1983
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…Gnas may couple Gprotein coupled receptor binding to AC activation. This result is supported by the previous findings: (1) AC was present in the stria vascularis and semicircular canal epithelium of the inner ear (Ahlstrom et al, 1975;Bagger-Sjoback et al, 1980;Anniko et al, 1981;Mees, 1984;Schacht, 1985;Oudar et al, 1990;Drescher et al, 2000).…”
Section: Effects Of Vasopressin On the Expression Of Genes Associatedsupporting
confidence: 94%
“…Gnas may couple Gprotein coupled receptor binding to AC activation. This result is supported by the previous findings: (1) AC was present in the stria vascularis and semicircular canal epithelium of the inner ear (Ahlstrom et al, 1975;Bagger-Sjoback et al, 1980;Anniko et al, 1981;Mees, 1984;Schacht, 1985;Oudar et al, 1990;Drescher et al, 2000).…”
Section: Effects Of Vasopressin On the Expression Of Genes Associatedsupporting
confidence: 94%
“…contains the highest activity of adenylate cyclase in the cochlea [1. 5,7]. Further, a correlation between the postnatal maturation of the ionic profile of endolymph and increasing strial adenylate cyclase activity was demonstrated biochemically [5].…”
Section: Introductionmentioning
confidence: 90%
“…Similar quantitative differences have been re ported for many enzyme systems responsible for K+-rich and NaMow content of endolymph during both the matu ration of endolymph [25] and at the adult stage [26], The increased concentration of endolymphatic K+ in the base [27] parallels the distribution of stria Na+-K+ ATPase [28] . However, anatomically the stria vascularis increases in thickness and surface area from apex to base.…”
Section: Discussionmentioning
confidence: 97%